2005
DOI: 10.1073/pnas.0506072102
|View full text |Cite
|
Sign up to set email alerts
|

Off-line learning of motor skill memory: A double dissociation of goal and movement

Abstract: Acquiring a new skill requires learning multiple aspects of a task simultaneously. For example, learning a piano sonata requires learning the musical notes and being able to implement this goal by learning the appropriate sequence of finger movements. After practice, skill continues to develop off-line during a period of consolidation. Here we show that different aspects of a procedural memory are processed separately during consolidation: Only the movement sequence is enhanced over the day; whereas only the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
279
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 240 publications
(316 citation statements)
references
References 28 publications
25
279
12
Order By: Relevance
“…Nonetheless, the time of retesting may influence the expression of off-line improvements. However contrasting improvements over a 12-hr interval -shown in an earlier study -against those that developed over the 24-hr intervals of the current study showed that goal and movement-based improvements can be equally expressed at 8am and at 8pm (Cohen et al 2005). Thus, time-of-day seems unlikely to have influenced the expression of offline learning.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…Nonetheless, the time of retesting may influence the expression of off-line improvements. However contrasting improvements over a 12-hr interval -shown in an earlier study -against those that developed over the 24-hr intervals of the current study showed that goal and movement-based improvements can be equally expressed at 8am and at 8pm (Cohen et al 2005). Thus, time-of-day seems unlikely to have influenced the expression of offline learning.…”
Section: Discussioncontrasting
confidence: 87%
“…Off-line improvements can be modified by a participant's ability to recall segments of the sequence (Robertson et al 2004). Those reporting four or less items consistently show goal-based improvements over a night of sleep and movement-based improvements over wake (Cohen et al 2005). We wished to examine the development of both types of improvement over a 24hr interval.…”
Section: Methods Participantsmentioning
confidence: 99%
See 3 more Smart Citations